Verruciform Xanthoma Presenting Within an Ear Piercing - Hannah E. Myers; Subhapradha Rangarajan; Michael Roberts; Christopher Buckley; Josh Hammel (Wolters Kluwer Medknow Publications, 2024)
Verruciform xanthomas are rare lesions affecting 0.025-0.5% of the population. They present as an asymptomatic, slow growing solitary lesion on the oral mucosa. Commonly misdiagnose as squamous cell carcinoma, verruca vulgaris, leukoplakia, and lichen planus. Presented is a 22 year old male with a painful verruciform xanthoma on the posterior ear lobe in a prior ear piercing.